2022
DOI: 10.3389/fimmu.2022.777724
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Nomogram to Predict Progression Based on the Circadian Clock and Insights Into the Tumor Immune Microenvironment in Prostate Cancer

Abstract: BackgroundCurrently, the impact of the circadian rhythm on the tumorigenesis and progression of prostate cancer (PCA) has yet to be understood. In this study, we first established a novel nomogram to predict PCA progression based on circadian clock (CIC)-related genes and provided insights into the tumor immune microenvironment.MethodsThe TCGA and Genecards databases were used to identify potential candidate genes. Lasso and Cox regression analyses were applied to develop a CIC-related gene signature. The tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 79 publications
2
22
0
Order By: Relevance
“…Clock mutations in colorectal cancer occurred in 53% of MSI, which could improve immunotherapy and chemotherapy (Alhopuro et al, 2010; Lin et al, 2020). Likewise, study observed consistent results regarding the impact of MSI on the progression‐free interval in prostate cancer patients (D. Feng et al, 2022). However, the impact of polymorphisms of the circadian rhythm genes on cancer development is highly dependent on the specific polymorphism and types of cancer (Morales‐Santana et al, 2019).…”
Section: The Function Of Circadian Rhythm In Cancersupporting
confidence: 61%
See 1 more Smart Citation
“…Clock mutations in colorectal cancer occurred in 53% of MSI, which could improve immunotherapy and chemotherapy (Alhopuro et al, 2010; Lin et al, 2020). Likewise, study observed consistent results regarding the impact of MSI on the progression‐free interval in prostate cancer patients (D. Feng et al, 2022). However, the impact of polymorphisms of the circadian rhythm genes on cancer development is highly dependent on the specific polymorphism and types of cancer (Morales‐Santana et al, 2019).…”
Section: The Function Of Circadian Rhythm In Cancersupporting
confidence: 61%
“…Clock mutations in colorectal cancer occurred in 53% of MSI, which could improve immunotherapy and chemotherapy (Alhopuro et al, 2010;Lin et al, 2020). Likewise, study observed consistent results regarding the impact of MSI on the progressionfree interval in prostate cancer patients (D. Feng et al, 2022).…”
Section: Epigenetic Variation Of Circadian Clock Gene Associated With...supporting
confidence: 55%
“…To date, it has been reported that TR genes are strong diagnostic and prognostic markers in cancers such as glioma [ 17 ], prostate cancer [ 18 ], and stomach adenocarcinoma [ 19 ]. However, studies that investigate whether TR genes can act as specific diagnostic biomarkers for psychiatric disorders to further explore relevant therapeutic targets for psychiatric disorders, especially MDD, are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Eight genes were selected by LASSO-Cox regression via the “glmnet” packages, and three hub genes (AHCYL2, ANKRD6, and FDGFRB) were finally screened by multivariate COX analysis with “both step” function. 30 The formula of CuPS was defined as follows: CuPS = −0.205*AHCYL2 exp + 0.231*ANKRD6 exp + 0.238*FDGFRB exp , where “exp” signifies the expression. The packages the “survivalROC” and “survminer” were utilized to compute the receiver operating characteristic curve (ROC) and Kaplan–Meier (K–M) survival curve.…”
Section: Methodsmentioning
confidence: 99%